Pengaruh Pemberian Arang Sekam Kayu Terhadap Pertumbuhan dan Hasil Tanaman Kangkung (Ipomoea reptans) - Udin, Mediyana; Sulha, Sulha (Peneliti.net, 2026)
This study aims to determine the effect of wood husk charcoal on the growth of kale (Ipomoea reptans) and to see the right dosage in plant cultivation. The study was conducted in Ampera Village, North Oba District, Tidore Islands City. for three months and took place in April-June 2025. This study used a randomized block design (RAK) with one treatment factor. The dosage of organic fertilizer Wood Husk Charcoal consisting of 5 levels, namely U0 (Without husk charcoal), U1 (400 g Husk Charcoal), and U2 (600 g Husk Charcoal), U3 (800 g Husk Charcoal), U4 (1000 g Husk Charcoal). So there are 5 treatments repeated 3 times, so there are 15 experimental units. The results of the analysis of variance showed that the application of organic fertilizer teak wood husk charcoal had a significant effect on the height of kale plants at the age of 15 HST, 20 HST, 25 HST and 30 HST. The difference in plant height occurs due to the provision of different concentrations of rice husk charcoal fertilizer, in the U0 treatment (without treatment) while in the U4 treatment with a concentration of 1000 grams of wood husk charcoal which shows the highest plant growth, this is because the nutrient content in the wood husk charcoal is absorbed by the plant. The provision of organic fertilizer wood husk charcoal has no significant effect on the number of leaves only at the observation age of 15 HST, and the parameter of the number of fresh weights reaches the highest results in the U4 treatment, while the lowest average value is in the U0 treatment. The results of fresh weight per plant show that the treatment of providing wood husk charcoal has a significant effect on fresh weight. The more wood husk charcoal given, the higher the fresh weight value of the kale plant